1993
DOI: 10.1002/1097-4679(199301)49:1<23::aid-jclp2270490104>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MMPI-2 scores of foreign Chinese and Caucasian-American students

Abstract: MMPI‐2 scores of foreign Chinese students (n= 25) were compared to those of a matched sample of Caucasian students (n = 21) and to normative data on American college students. Although responses for all groups were within normal limits, Chinese men appeared more socially introverted than Caucasian men. Relative to Caucasian women, Chinese women were more defensive, depressed, unaware of somatic and psychosocial problems, and gender astereotypic in interests. These tentative findings are discussed in terms of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 6 publications
1
16
0
3
Order By: Relevance
“…I heard that he had always been like that -always alone. (Wenchun, October 20, 2008) To an extent, our experiences echo some previous personality studies on overseas Chinese students (Cheung, Conger, Hau, Lew, & Lau, 1992;Stevens, Kwan, Graybill, 1993). According to these two empirical studies conducted in the early 1990s, basic continuities are evident in the personality traits of mainland and overseas Chinese despite some superficial discontinuities (Cheung, et al, 1992).…”
Section: Personalitysupporting
confidence: 80%
See 1 more Smart Citation
“…I heard that he had always been like that -always alone. (Wenchun, October 20, 2008) To an extent, our experiences echo some previous personality studies on overseas Chinese students (Cheung, Conger, Hau, Lew, & Lau, 1992;Stevens, Kwan, Graybill, 1993). According to these two empirical studies conducted in the early 1990s, basic continuities are evident in the personality traits of mainland and overseas Chinese despite some superficial discontinuities (Cheung, et al, 1992).…”
Section: Personalitysupporting
confidence: 80%
“…In a North American setting, Chinese graduate students tend to be introverted, requiring more time to build friendships than they would on their home soil. As it is difficult to separate personality and culture, updated and qualitative studies on personality (especially in relation to culture) are necessary to examine this important factor among Chinese graduate students in North America (Stevens, et al, 1993).…”
Section: Personalitymentioning
confidence: 99%
“…This non-effect seems to fly in the face of the many demonstrations of an AH-EH shyness differential in self-reports (e.g., Dion & Yee, 1987;Eysenck, & Eysenck, 1980;Furnham & Cheng, 1999;Fukuyama & Greenfield, 1983;Iwawaki, Johnson & Marsella, 1978;Loo & Shiomi, 1982;Lynn & Thompson, 1975;Magnusson et al, 1983;McCrae et al, 1998;Sofue, 1979;Stevens, Kwan, & Graybill, 1993;Thompson, Ishii, & Klopf, 1990;Thompson, Klopf, & Ishii, 1991;Windle et al, 1987;Zhang et al, 1999). Surely, the questions posed in those studies were not all interpreted as referring to classroom shyness.…”
Section: Study 3: Audience Effects In Social Shynessmentioning
confidence: 99%
“…In addition, as mentioned above, when the scores of Chinese normal respondents were compared to American respondents, research indicated that the former were elevated on a number of validity and clinical scales (Cheung et al, ; Kwan, ; Stevens et al, ). As a result, we made the following third hypothesis.
Hypothesis 3 : The best cut‐off scores (raw scores) of the indices would be higher than those obtained from the studies using the English MMPI‐2.
…”
mentioning
confidence: 97%
“…The Chinese MMPI‐2 was published in 2003 (Cheung, Zhang, & Song, ). When the scores of Chinese normal respondents were compared to American respondents, research indicated that the former were elevated on a number of validity and clinical scales, for example, the scales Lie, Infrequency, Depression, Schizophrenia, and Social Introversion (Cheung et al, ; Kwan, ; Stevens, Kwan, & Graybill, ). Accordingly, we should be cautious in cross‐cultural comparisons of the MMPI‐2 scores.…”
mentioning
confidence: 99%